Elementary School Teachers‟ Knowledge, Attitudes, and Challenges in Dealing with Conduct Disorders Children within their Regular Classrooms - Khali, Amal I. (International Journal of Psychosocial Rehabilitation, 2020)
Background: Conduct disorders are a repetitive and persistent pattern of behavior in which the basic rights of others or major age-appropriate societal norms or rules are violated. The prevalence of conduct disorder is high in Saudi Arabia and worldwide. The aim of the current study was to assess the knowledge and attitude of general education elementary school teachers toward inclusion of children with conduct disorders in their regular classes. Methods: a quantitative descriptive cross-sectional study design was used with 100 elementary teachers recruited conveniently form four schools located in south Jeddah, Saudi Arabia. Three tools were used to achieve the current study objectives, which are conduct knowledge, and attitude scale. Data were collected after receiving officials’ approvals and ensuring validity and reliability of the tools. Results: the findings revealed that majority 85% of studied teachers had poor knowledge and negative attitudes toward inclusion of conduct disorders in their regular classes, there is no correlation between the demographic and knowledge and attitude, and between the challenges and knowledge and attitude. Nevertheless, there are positive correlation between the knowledge and attitude at p≥0, 05. Conclusion: the findings of the current study revealed that teachers had poor knowledge and negative attitude. Additionally, there was no significant correlation between the demographic background of the respondents, knowledge and attitude, and between their challenges, knowledge and attitude. However, the more the knowledge and teaching experiences teachers had the more the favorable attitudes toward the inclusion of conduct disorders children in the mainstream school will be. Therefore, a furtherance of this study could also explore the impact of a training program.